2022
DOI: 10.7759/cureus.23103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Determinants of Mortality in Patients With COVID-19: A Retrospective Analytical Cross-Sectional Study in a Tertiary Care Center in South India

Abstract: IntroductionThe COVID-19 pandemic gained ground in India, starting from a few cases and spreading to the whole country; eventually becoming the second-most affected country worldwide. Here, we present the clinical and laboratory profile and the risk factors associated with mortality in COVID-19. The study comes from Kerala, a region that reported the first case in India. Kerala has the second-highest case burden in the country but also has managed to keep the case fatality rate down below the national average.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…Moreover, CMV positive patients younger than 87 years had a higher risk of in-hospital mortality than those without CMV reactivation. Consistent with other investigations, we also found that CRP, neutrophil count and frailty status were significantly associated with in-hospital death [ 33 , 34 , 35 ], whereas in patients older than 87 years, who were more susceptible to mortality from SARS-CoV-2 infection with respect to the younger group (45% vs. 17%), CMV DNAemia was not associated with death. In accordance with previous evidence, in the oldest group the main factors related to in-hospital mortality were age and an increased neutrophil count [ 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, CMV positive patients younger than 87 years had a higher risk of in-hospital mortality than those without CMV reactivation. Consistent with other investigations, we also found that CRP, neutrophil count and frailty status were significantly associated with in-hospital death [ 33 , 34 , 35 ], whereas in patients older than 87 years, who were more susceptible to mortality from SARS-CoV-2 infection with respect to the younger group (45% vs. 17%), CMV DNAemia was not associated with death. In accordance with previous evidence, in the oldest group the main factors related to in-hospital mortality were age and an increased neutrophil count [ 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our earlier analysis, ANC, CRP, D-dimer, and BUN were shown to be independent predictors of COVID-19-related mortality [ 20 ]. Cut-off values predicting mortality were derived for the same biomarkers in the present analysis in both group A and group B. ANC and D dimer showed lower cut-off values in group B when compared to group A while CRP and BUN demonstrated a higher cut-off in group B.…”
Section: Resultsmentioning
confidence: 99%
“…This is one of the limitations of our study. In fact, hypertension was the second highest comorbidity in our study population [ 20 ]. Other limitations that could have affected the results are the smaller sample size and the retrospective nature of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation